Dreaming of God: a critical re-evaluation of Shakespeare's theological context, with particular reference to 'Hamlet' - Down, Therese Marie (2025)
Dominant Material Shakespeare criticism treats religion as pre-modern and not seriously influential in the plays, beyond its political use in oppressive popular control. Postmodern and Marxist critiques detect secularity in Shakespeare and generally posit as its source Florio’s translation of Montaigne’s Essays, which could have caused a Shakespearean turn to Epicurean ‘atomism’ or Renaissance scepticism. Other critiques assume a contextual Calvinist consensus, and see in the Tragedies a theistically-eliminative defiance of a tyrannical deus absconditus, whose pre-Fall consignment of humanity to salvation or preterition renders redemptively-desperate any human free will exercise to choose or avoid sin. Christian doctrine is not frequently explored positively in relation to Shakespeare’s work. This thesis detects, in Shakespeare’s key Tragedies, a possible sympathy with a contemporary via media Protestant theology which rebuked Reformed, soteriological orthodoxy. Exemplified by Philip Melanchthon, then Richard Hooker, this irenic strain of Christianity anticipated Arminianism by several decades. Approached from a consideration of this theology’s insistence on universally-offered salvation, life-long effectiveness of penance, and the free will of people to choose or reject moral evil, the plays reveal a seminal concern with the redemptive power of repentance, the efficacy of mercy, and that Shakespeare’s most vicious characters are least exercised by fear of damnation. This seems indicative of a theodical paradigm wherein divine judgment is contingent and people, not God, cause evil. Hamlet is frequently offered as evidence of Shakespeare’s sceptical mindset. New Historicists make much of the Protestant rejection of transubstantiation to indicate, in Hamlet, a Shakespearean contempt for all metaphysics. Some detect in the play a Montaignian influence to Lucretian atomism or Pyrrhonic Scepticism, while Calvinist readings emphasise Shakespeare’s disaffection for orthodox, predestination doctrine which damns Claudius and dooms Hamlet. None values the Ghost. This thesis proposes readings of Hamlet emerging from a rigorous re-evaluation of Shakespeare’s post-Reformation context.